1999
DOI: 10.1016/s0079-6611(99)00024-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of atmospheric deposition in the biogeochemistry of the Mediterranean Sea

Abstract: Estimates of atmospheric inputs to the Mediterranean (MED) and some coastal areas are reviewed, and uncertainities in these estimates considered. Both the magnitude and the mineralogical composition of atmospheric dust inputs indicate that eolian deposition is an important (50%) or prevailing (>80%) contribution to sediments in the offshore waters of the entire Guerzoni et al.,"The role of atmospheric deposition in the biogeochemistry of the Mediterranean Sea"2 Mediterranean (MED) basin. Model data for trace m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
287
1
21

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 391 publications
(325 citation statements)
references
References 79 publications
16
287
1
21
Order By: Relevance
“…1) receives some of the highest fluxes of atmospheric aerosols from natural and anthropogenic sources (14,15). The Sahara desert in Africa is the major source of natural aerosols to the Mediterranean and the main external source of nutrients for the sea's surface waters during summer (14).…”
Section: Resultsmentioning
confidence: 99%
“…1) receives some of the highest fluxes of atmospheric aerosols from natural and anthropogenic sources (14,15). The Sahara desert in Africa is the major source of natural aerosols to the Mediterranean and the main external source of nutrients for the sea's surface waters during summer (14).…”
Section: Resultsmentioning
confidence: 99%
“…5). In addition to riverine inputs, atmospheric inputs, which are high across the Mediterranean (Guerzoni et al, 1999), are an important source of organic carbon (Dachs et al, 2005;Jurado et al, 2008), providing, along with riverine inputs, the allochtonous carbon required to support net heterotrophic communities.…”
Section: Discussionmentioning
confidence: 99%
“…Regaudie-de-Gioux (aurore.regaudie@uib.es) position across the entire basin, from riverine inputs (Martin et al, 1989;Bethoux and Gentili, 1999;Guerzoni et al, 1999), and from inputs with Atlantic water entering the Western basin. Hence, nutrient inputs are highest in the Western basin, which receives the largest riverine discharge (e.g.…”
Section: Correspondence Tomentioning
confidence: 99%
“…Guerzoni et al (1999) and Kallos et al (2005) found that approximately 10 8 metric tons of dust are deposited annually over the Mediterranean Sea, and a similar amount is transferred towards Europe. In particular, the deposition rate of Saharan dust in the Mediterranean has been estimated to 3-14 g/m 2 per year with the largest value found for the Eastern Mediterranean (Prospero, 1996).…”
Section: Introductionmentioning
confidence: 94%